Impact of oregano (Origanum vulgare) supplementation on antioxidant status, and related gene expression in Black Sea salmon, Salmo labrax - Özel, OT; Düzgüneş, ZD; Gürkan, SΕ; Çakmak, E (Journal of the Hellenic Veterinary Medical Society, 2024)
The aim of this study was to to evaluate the effect of diets containing 0, 50, 100, 200, and 400 mg kg-1 oregano (Origanum vulgare) essential oil on antioxidant enzymes (CAT, GPx and SOD) in liver and muscle tissues and expression levels of their-relevant genes of Black Sea salmon (Salmo labrax) juvenile. This study was conducted in the freshwater recirculating aquaculture system (RAS). Fish with average initial weights of 3.52±0.01g were distributed randomly in triplicate to 50 liter fiberglass tanks, and 45 fish were placed in each experimental tank. Fish were fed 3% level of live weight for 90 days. The addition of oregano essential oil had no significant impacts on CAT in liver and GPx in muscle (p>0.05), but increased SOD activity was observed in muscle. The increased GPx genes expression were observed in both muscle and liver tissues. The addition of oregano essential oil had no significant impacts on the mRNA expression of SOD in muscle, nevertheless increased SOD genes expression were determined in liver. In terms of the mRNA expression of CAT, control and 200 mg kg-1 concentration were similar to each other and had the highest level. Present study suggests that the addition of oregano essential oil can enhanced the antioxidant enzyme activities, and related gene expression of Black Sea salmon (Salmo labrax) juvenile.